Socialización de la ordenanza de control y protección de fauna urbana en Quito. - Torres Vaca, María Sol (2016)
In this academic article I analice the socialization of the Quito Council Ordinance # 048 under an educomunicative lecture, in Pomasqui population with regard to the abuse of the animals that they live with. The reader will be able to know and take a posture about this situation. Thus, this article presents the problem and calls for a possible solution. In 2011, bylaw 048 became applicable in Quito with the purpose of decreasing animal abuse in the city. In the place of the investigation, it was detected a shortcoming in the application of the ordinance. The main failure is the lack of preoccupation to socialize it from the Local Council of Quito –responsible entity to told it and to enforce it– to the people of Pomasqui–northwest of Cantón Quito–. Additionally, people in this place show a general lack of interest in improving or changing their bad attitude toward animals –education and respect to the environment–. Both are related with the communicative aspect and the community development. Therefore, the proposals and recommendations are based in these two elements of the citizen activity. So, the achievement is in the educomunicative field, specially under the community and critical presumptions of the communication that manage Habbermas and Kaplún and a philosophical central concept from the Sumak Kawsay worldview legislated by the Ecuadorian Constitution. Consequently, these laws watch for the healthy coexistence between humans and living creatures that are in the nature; questioning the animal abuse and the breaches of the regulations.